The mapping of mRNA alterations elucidates the etiology of radiation-induced pulmonary fibrosis - Yuan, Meng; Zhao, Maoyuan; Sun, Xin; Hui, Zhouguang (Frontiers in Genetics, 2022)
Background: There is no definite conclusion of the etiology of radiation-induced pulmonary fibrosis, and the effective interventions are still lacking. In this study, based on radiation-induced pulmonary fibrosis mouse model, we aim to identify genes responsive to irradiation, compare the difference in genome expression between normal lung tissues and the irradiated ones, and to provide the mRNA alteration mapping that can make the predictive model and potential interventions of radiation-induced pulmonary fibrosis. Methods: C57BL/6 mice were exposed to a single 16Gy or 20Gy thoracic irradiation to establish the radiation-induced pulmonary fibrosis mouse model. Lung tissues were harvested at 3 and 6 months after irradiation for histological identification. The global gene expression of lung tissues was assessed by RNA sequencing. Differentially expressed genes were identified and subjected to functional and pathway enrichment analysis. Infiltration of immune cells was evaluated by CIBERSORT. Results: At 3 months after radiation, 317 mRNAs were significantly upregulated and 254 downregulated in the 16 Gy group. 203 mRNAs were upregulated and 149 downregulated significantly in the 20 Gy group. At 6 months after radiation, 651 mRNAs were significantly upregulated and 131 downregulated in the 16 Gy group. 106 mRNAs were significantly upregulated and 4 downregulated in the 20 Gy group. Several functions and pathways including angiogenesis, epithelial cell proliferation, extracellular matrix, complement and coagulation cascades, TNF signaling pathway, NOD-like receptor signaling pathway, HIF-1 signaling pathway, cellular senescence, myeloid leukocyte activation, regulation of lymphocyte activation, mononuclear cell proliferation, immunoglobulin binding were significantly enriched in irradiation groups based on the differentially expressed genes. Conclusions: Irradiation responsive genes were identified. The differentially expressed genes were mainly associated with cellular metabolism, epithelial cell proliferation, cell injury, and immune cell activation and regulation.